Evaluating the Effectiveness of The Smarts Didi Model in Enhancing Teacher Competency for Differentiated Instruction in Indonesia: A Confirmatory Factor Analysis Approach - Anis Cholis; Ribut Margo Mulyanto; Achmad Yusuf; Sari Cahya Putri; Tuti Mutia (International Journal of Geography, Social, and Multicultural Education, 2026)
This study evaluates the effectiveness of the SMART DiDi Model (Strategic Modelling of the Merdeka Pathway and Digital Differentiation) in enhancing teacher competency for differentiated instruction in Indonesia. With the increasing emphasis on student-centered learning, many educators face challenges in adapting instructional strategies to accommodate diverse student needs. This research employs a quantitative approach using a descriptive and inferential design, involving 207 social studies teachers from public senior high schools in Bojonegoro. Data were collected through a structured questionnaire distributed via Google Forms and analyzed using Confirmatory Factor Analysis (CFA) in R Studio with Maximum Likelihood Robust (MLR) estimation. Model fit was assessed using statistical indicators such as Chi-square (χ²), Standardized Root Mean Square Residual (SRMR), Comparative Fit Index (CFI), and Root Mean Square Error of Approximation (RMSEA). The findings indicate that SMART DiDi significantly enhances teachers' instructional effectiveness, particularly in lesson planning, student engagement, and the application of differentiation strategies. Teachers reported high levels of satisfaction and confidence in implementing SMART DiDi, with CFA results confirming the validity and reliability of the model. As a structured, technology-integrated framework, SMART DiDi offers a sustainable and scalable approach to teacher professional development. This study recommends that educational institutions adopt SMART DiDi as a standardized training framework, aligning with the principles of Education 4.0 and the Merdeka Curriculum, to optimize school mentoring in the implementation of differentiated instruction.